Fetomaternal outcome in patients with diabetes mellitus in pregnancy - Shingala, Kaveri D.; Shah, Sapana R.; Vyas, Rupa C.; Parikh, Purvi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Diabetes mellitus (DM) is defined as increased blood glucose level due to defect in insulin secretion, insulin action or both. Undiagnosed or inadequately treated diabetes mellitus during pregnancy can lead to significant maternal and fetal complications. The study was conducted to review feto-maternal outcome in pregnancy with diabetes and to plan management of pregnancy with diabetes and to study the modalities for treatment of DM in pregnancy. Methods: A prospective case study was conducted from July 2015 to December 2018 at a tertiary care center. Study group used single step 75gm oral glucose tolerance test (OGTT) test recommended by WHO for GDM diagnosis. Results: GDM (85%) was more common than overt diabetes (15%) and in younger age group (53.75%) and Multiparous patients (18.2%). Most of patients required insulin (81.2%) for treatment of DM during pregnancy along with medical nutrition therapy and exercise. Most common association in this patient was hypertension (41%). Rate of caesarean section (60%) was more common. Average birth weight was of >3.5 kg, intrauterine death (4.2%), preterm delivery (14.2%) and admission to NICU were also common. Conclusions: There was significant fetomaternal morbidity in patients with diabetes mellitus. Early diagnosis and treatment reduces the fetomaternal outcome.